Self‐regulation deficits moderate treatment outcomes in a clinical trial evaluating just‐in‐time adaptive interventions as an augmentation to cognitive‐behavioral therapy for bulimia‐spectrum eating disorders. Issue 5 (24th February 2022) - Presseller, Emily K.; Wilkinson, Megan L.; Trainor, Claire; Lampe, Elizabeth W.; Juarascio, Adrienne S.
Abstract: Objective: Just‐in‐time adaptive interventions (JITAIs), momentary interventions delivered at identified times of risk, may improve skill utilization during cognitive‐behavioral therapy (CBT‐E) for bulimia‐spectrum eating disorders (BN‐EDs). JITAIs may be especially helpful for individuals with self‐regulation deficits, including emotion regulation deficits and elevated impulsivity. Method: Participants ( N = 55 with BN‐EDs) received 16 sessions of CBT‐E with electronic self‐monitoring and were randomized to receive JITAIs (JITAIs‐On) or not receive JITAIs (JITAIs‐Off). Baseline Difficulties in Emotion Regulation Scale (DERS) and UPPS‐P Impulsive Behavior Scale (UPPS‐P) total scores were examined as moderators of baseline to post‐treatment change in binge episodes, compensatory behaviors, and Eating Disorder Examination (EDE) global score using repeated measures ANOVAs. Results: Emotion regulation difficulties significantly moderated compensatory behavior change ( F [1, 51] = 4.31, p = .04, ηp 2 = 0.08) such that individuals with emotion regulation deficits demonstrated greater improvements in the JITAIs‐On condition. Impulsivity moderated change in binge episodes ( F [1, 51] = 8.94, p = .004, ηp 2 = 0.15) and compensatory behaviors ( F [1, 51] = 7.83, p = .007, ηp 2 = 0.13), such that individuals with high impulsivity showed greater improvement in the JITAIs‐On condition. Neither DERS nor UPPS‐P scores moderated EDE global score change. Discussion: JITAIs appear particularly beneficial for facilitating skill use during treatment for BN‐EDs for individuals with self‐regulation deficits, yielding improved treatment outcomes. Public Significance Statement: Reminders to use therapy skills that are delivered via smartphone as an individual goes about their daily life may improve treatment response among individuals with bulimia nervosa who have difficulty coping with emotions or who tend to act impulsively. Results from this study indicate that individuals with these difficulties benefitted more from cognitive‐behavioral therapy when it was accompanied by in‐the‐moment reminders to use therapeutic skills, which may facilitate long‐term recovery. Clinical Trials.gov Registration Number: NCT03673540.